Reflections of the COVID-19 Pandemic on Instrument Training in a Conservatory - Kara, Derya Atik; Kara, Melih (Fırat University, 2023)
The study aims to determine reflections of the COVID-19 pandemic and the emergency remote teaching process on the instrument training carried out in a conservatory of a state university in Turkey. In line with this purpose, the perspectives of lecturers, students, and parents within the Music Department were gathered using qualitative research methods. The study revealed that the emergency remote teaching process presented challenges, particularly in technical aspects and student interaction, and proved to be ineffective for instrument education. Given that, it also provided students with opportunities to explore alternative learning methods, such as utilizing audio and video recordings. Despite efforts to address practice-related issues, participants believed that face-to-face training would be more effective in overcoming deficiencies. The study concluded that the problems encountered during emergency remote teaching primarily stemmed from the ineffective implementation of distance learning and insufficient participant experience in this domain. Consequently, for distance education to be considered a viable option in music education, music educators need to undergo well-planned and comprehensive distance learning programs in suitable conditions. Such experiences could potentially reshape their perspectives and foster a more favorable view of distance education.

Bu araştırma kapsamında konservatuvarda yürütülen çalgı eğitimine COVID-19 pandemisinin ve acil uzaktan öğretim sürecinin yansımalarının belirlenmesi amaçlanmaktadır. Temel nitel araştırma ile desenlenen araştırmanın amacı doğrultusunda konservatuvar bünyesinde bulunan Müzik Bölümünde görevli öğretim elemanlarının, farklı çalgılara ilişkin öğrenim gören, farklı sınıflardaki öğrencilerin ve velilerin görüşleri alınmıştır. Araştırmada çalgı eğitiminde acil uzaktan eğitim sürecinin özellikle teknik konular ve etkileşim konularında yoğunlaşan çeşitli sorunlara neden olduğu ve enstrüman eğitiminde etkili olmadığı düşüncesi hakimdir. Bunun yanında eğitim sürecinde ses ve görüntü kayıtlarının kullanılması gibi enstrüman eğitimine yönelik farklı öğrenme yollarının denenmesine olanak tanıdığı söylenebilir. Enstrüman çalışırken yaşanan sorunların çözümüne yönelik çaba harcandığı ancak eksiklerin çoğunlukla yüz yüze eğitimde kapatılacağı inancı olduğu görülmüştür. Araştırma sonuçlarına dayalı olarak yaşanan sorunların çoğunlukla uzaktan öğretimin etkili bir şekilde kullanılmamış olması ve katılımcıların bu konuda yeterli deneyime sahip olmamasından kaynaklandığı söylenebilir. Müzik eğitimcilerinin uygun koşullar altında, nitelikli ve planlanmış bir uzaktan öğrenme sürecini deneyimlemeleri durumunda bakış açılarının değişebileceği ve uzaktan eğitimin bir seçenek olarak müzik eğitiminde kullanımının önünün açılabileceği söylenebilir.
COVID-19 PANDEMİSİNİN KONSERVATUVARDAKİ ÇALGI EĞİTİMİNE YANSIMALARI
Keywords: Other Fields of Education (Other); Alan Eğitimleri (Diğer)